The Management Of Conflict In Buyer-Seller Relationships: A Case Study Of An Australian Exporter In Asian And Us Markets - Freeman, Susan (Asian Academy of Management (AAM), 2003)
This paper will extend the conflict management stream by examining the complexity of conflict in buyer-seller relationships, comparing Western and Asian markets and their "contextual boundaries". Specifically, a model is developed linking different dimensions of cross-cultural business relationships to different dissolution and communication strategies for managing conflict. Multiple in-depth interviews in a single case study provide support for the theoretical development of a model of five key factors important in the selection of appropriate conflict management styles by the focal firm when managing buyer relationships in psychically distant markets.